Pengaruh Latihan Batuk Efektif Dan Fisioterapi Dada Terhadap Pengeluaran Sputum Pada Pasien Penyakit Paru Obstruksi Kronik Di Rs Khusus Paru Karawang - Ahmad Miftah Anas; Liza Agustin; Bibit Tri Wahyudi (LPPM STIKES Siti Hajar dan Insight Power, 2023)
COPD is a chronic obstructive pulmonary disease characterized by severe airway obstruction or lung inflammation that develops over a long period of time. Which is characterized by difficulty breathing, coughing up phlegm, and wheezing or wheezing. Minimizing airway obstruction can be done by means of effective coughing exercises and chest physiotherapy. This study aims to determine the effect of effective cough and chest physiotherapy on sputum production in COPD patients at the Karawang Lung Special Hospital. Where the respondents in this study amounted to 20 respondents. This research was conducted in the Inpatient Room of the Karawang Lung Special Hospital. This research method is pre-experimental pre-test and post-test with total sampling technique. The population in this study was COPD patients who experienced airwaydisorders or inflammation of the lungs, totaling 20 people. The results of the McNemar test obtained p value P = 0.000 (p < 0.05) which means that there is an effect of effective coughing exercises and chest physiotherapy on sputum production in COPD patients. The results showed that there was a difference before the intervention of expelling sputum of 3 respondents, after the intervention of expelling sputum of respondents, as many as 19 people. Thus, what is obtained from the study is that there is an effect of effective coughing exercises and chest physiotherapy on sputum production in COPD patients inthe Inpatient Room of Khusu Pulmonary Hospital Karawang. Keywords: : Effective cough and chest physiotherapy, sputum production, COPD